Obstacles In Learning at SDN 21 Sungai Kakap During The Covid 19 Pandemic - Syahadatina; Daryanto, Zusyah Porja (Journal Sport Academy, 2022)
The purpose of this study is to determine the barriers to learning during the Covid 19 pandemic. This research is descriptive research with qualitative approach. The location in this study is SDN 21 Sungai Kakap. This study involved several participants, namely: all teachers and upper class students of SDN 21 Sungai Kakap. Data collection techniques used in the form of in-depth interviews and observation techniques. Data analysis is qualitative data analysis, namely: 1. Observation. 2. Data reduction 3. Presentation of data 4. Conclusion making. Based on the results in the study, it can be concluded that the obstacles in learning during the covid 19 pandemic are as follows: 1. Internal factors (subject matter, learning process, assignment, and financial related Economics) and 2. External factors (facilities, Learning Media, and quotas/signals).